2011
DOI: 10.2298/vsp1102130r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron supplementation on maximal oxygen uptake in female athletes

Abstract: VO2max was significantly lower in the iron deficient anemic group versus the latent iron deficient group. Iron supplementation during a two-month training period significantly improved body iron status in the iron deficient female athletes with or without anemia, and significantly increased VO2max only in the subjects with iron deficiency anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…Of the 45 athletes screened, 15 (nine female athletes: age, 21 T 2 yr; height, 169.1 T 4.0 cm; body mass, 59.3 T 4.3 kg; V O 2max , 64.5 T 5.7 mLIkg j1 Imin j1 ; and six male athletes: age, 20 T 1 yr; height, 178.8 T 5.9 cm; body mass, 65.2 T 3.5 kg; V O 2max , 76.7 T 2.7 mLIkg j1 Imin j1 ) were classified as irondeficient but not anemic (females: sFer G 30.0 KgIL j1 , Hb 9 12.0 gIdL j1 ; males: sFer G 40 KgIL j1 , Hb 9 12.0 gIdL j1 ). It is acknowledged that there is no universal consensus for the classification of IDNA in athlete populations, with a variety of cutoffs for sFer appearing in the literature (3,9,29). An upper limit of 40 KgIL j1 is used in the present investigation for male athletes because this is considered iron deficient by the national governing body for track and field to which the athletes are affiliated with and whereby medical practitioners would treat and monitor the iron status of each athlete.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 45 athletes screened, 15 (nine female athletes: age, 21 T 2 yr; height, 169.1 T 4.0 cm; body mass, 59.3 T 4.3 kg; V O 2max , 64.5 T 5.7 mLIkg j1 Imin j1 ; and six male athletes: age, 20 T 1 yr; height, 178.8 T 5.9 cm; body mass, 65.2 T 3.5 kg; V O 2max , 76.7 T 2.7 mLIkg j1 Imin j1 ) were classified as irondeficient but not anemic (females: sFer G 30.0 KgIL j1 , Hb 9 12.0 gIdL j1 ; males: sFer G 40 KgIL j1 , Hb 9 12.0 gIdL j1 ). It is acknowledged that there is no universal consensus for the classification of IDNA in athlete populations, with a variety of cutoffs for sFer appearing in the literature (3,9,29). An upper limit of 40 KgIL j1 is used in the present investigation for male athletes because this is considered iron deficient by the national governing body for track and field to which the athletes are affiliated with and whereby medical practitioners would treat and monitor the iron status of each athlete.…”
Section: Methodsmentioning
confidence: 99%
“…16 Some (but not all) RCTs have shown that iron improves aerobic 17 and endurance capacity, 18 cognitive performance, 19 productivity, 20 symptomatic fatigue, 21 and mood 22 in iron-depleted nonanemic women.…”
Section: Effects Of Iron Supplementation In Nonpregnant Womenmentioning
confidence: 99%
“…3). When the 20 anemic participants from the single trial recruiting iron-deficient anemic women (30) were removed from the analysis, the beneficial effect from iron remained significant [MD: 2.18 (95% CI: 0.57, 3.79), P = 0.008, I 2 = 72%], as it did when the 1 trial that recruited 42% male participants (31) was excluded [MD: 2.25 (95% CI: 0.70, 3.80)]. The effect was seen in irondeficient women, although there was also a benefit in women for whom iron status had not been determined at recruitment.…”
Section: Maximal Exercise Performancementioning
confidence: 99%